The paradoxes of the Mapuche people: a right to self-determination? Free internal or external? (Revista LIDER, 2020)
Historically, the Mapuche people had always shown full exercise of their right to external self-determination. However, with the centuries, the Mapuche people have moved toward a different situation. This essay focus on the situation of the Mapuche people in the Chilean State and the external self- determination, rescuing it from oblivion through three principles of international law: the principle of continuity of border treaties, the principle of inviolability of borders and the uti possidetis juris. On the other hand, the approach of the Mapuche conflict, from the institutions and society as a whole, requires passage through the treatment of three main areas of discussion: the right to land and natural resources, the reparation of the historic debt and the recognition of its status as a people.